INDONESIAN CULTURAL ANALYSIS IN THE SONG OF â€œLATHIâ€ BY WEIRD GENIUS - Khusna, Febriana Aminatul; Khoiruddin, Muhammad; Indriani, Giwang (Kementerian Pendidikan dan Kebudayaan, 2021)
Culture is something that cannot be separated in daily life. Thus, the importance of cultural preservation has become a major topic in the modern era. Music is a media that can be used to introduce the culture. This study aimed to investigate the Indonesian cultural elements contained in the song of